Twenty-Week Dietary Supplementation with Beeswax Alcohol (BWA; Raydel®) Ameliorates High-Cholesterol-Induced Long-Term Dyslipidemia and Organ Damage in Hyperlipidemic Zebrafish in a Dose-Dependent Manner: A Comparative Analysis Between BWA and Coenzyme Q10 - Kyung-Hyun Cho; Ashutosh Bahuguna; Yunki Lee; Sang Hyuk Lee; Ji-Eun Kim (Pharmaceuticals)
Background/Objectives: Beeswax alcohol (BWA; Raydel®) is a blend of six long-chain aliphatic alcohols extracted from honeybee wax and is well known for its diverse functionality and health benefits. Herein, the efficacy of a BWA dietary intervention for 20 weeks was assessed to ameliorate high-cholesterol diet (HCD)-induced dyslipidemia and adverse effects on the vital organs of adult zebrafish. Methods: Adult zebrafish were fed different high-cholesterol diets (HCDs; final concentration of 4%, w/w) supplemented with BWA (final concentrations of 0.1%, 0.5% and 1.0%, w/w) or CoQ10 (final concentration of 1.0%). Following 20 weeks of supplementation, blood and different organs (liver, kidney, testes and ovaries) were collected, and biochemical, histological and immunohistochemical analyses were performed. Results: The results demonstrate a dose-dependent effect of BWA of mitigating HCD-induced mortality in zebrafish over the 20-week supplementation period, which was noticeably better than the effect exerted by coenzyme Q10 (CoQ10). Consistently, a dose-dependent effect of BWA consumption of curtailing HCD-induced total cholesterol (TC) and triglyceride (TG) levels and increasing high-density-lipoprotein cholesterol (HDL-C) levels was noticed. Compared with CoQ10 (final concentration of 1.0%, w/w), BWA (final concentration of 1.0%, w/w) displayed a significantly better effect of mitigating HCD-induced dyslipidemia, as evidenced by 1.2-fold (p < 0.05) and 2.0-fold (p < 0.05) lower TC and TG levels and 2.4-fold (p < 0.01) higher HDL-C levels. The histological analysis revealed substantial prevention of fatty liver changes, reactive oxygen species (ROS) generation, cellular senescence and interleukin (IL)-6 production in the hepatic tissue of BWA zebrafish, which was significantly better than the effect exerted by CoQ10. Consistently, compared with CoQ10, significant 25% (p < 0.05) and 35% (p < 0.01) reductions in the HCD-induced elevated levels of the hepatic function biomarkers aspartate aminotransferase and alanine aminotransferase was observed in the BWA group. Likewise, BWA consumption efficiently ameliorated HCD-induced kidney, ovary and testis damage by inhibiting ROS generation, cellular senescence and lipid accumulation. Conclusion: Supplementation with BWA demonstrated higher therapeutic potential than that with CoQ10 to prevent dyslipidemia and organ damage associated with long-term consumption of HCDs.